The Effect of a Quizizz Assisted Gamified Learning Model on the Mathematical Problem-Solving Skills of 10th-Grade High School Students - Utami, Luthvia Aprilliza; Rosliana Harahap (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The research aims to find out the effect of the gamification learning model using Quizizz on students’ mathematical problem-solving ability that focuses on Systems of Linear Equation Problems with Three Variables (SPLTV). This research used a quantitative method with a quasi-experimental design of nonequivalent control groups. The population was 660 tenth-grade students in MAN 2 Model Medan in the 2025/2026 academic year. Purposive sampling was used to take Class X-Q (n=32) as the experimental group and Class X-R (n=30) as the control group. Nine validated essay items (four pretest and five posttest questions) were used for data collection and met all standard psychometric criteria for validity, reliability, difficulty level, and discrimination index. Pre-analysis assumptions were satisfied, with the Shapiro–Wilk test confirming a normal distribution (0.202, 0.486, 0.172, and 0.133) and Levene’s test demonstrating variance homogeneity (0.414). The independent samples t-test revealed a statistically significant difference (p = 0.002 < 0.05), with the calculated t-value (t = 3.22) exceeding the critical t-threshold (2.000). Furthermore, the experimental cohort achieved a higher posttest mean score (86.78) than the control cohort (81.43), yielding a substantial effect size (Cohen’s d = 0.819). These outcomes indicate that integrating gamification via Quizizz substantially enhances students’ mathematical problem-solving skills. The distinct novelty of this research lies in implementing this digital gamification framework for SPLTV instruction while assessing problem-solving performance through Polya’s framework. Future investigations are encouraged to extend this model to alternative mathematical topics, diverse educational levels, or additional learning variables.